Behaviour of grid connected photovoltaic systems - Azuki, Abdul Salam; Ismail, Adam; Fatimah Zaharah, Hamidon; Haidar, Ahmed M. A. (IEEE, 2011)
The grid connected photovoltaic is one of the expected local power supply system that consists of distributed generators, loads, power storage devices, heat recovery and power electronics equipments. In this paper, a grid connected Photovoltaic (PV) energy system is presented to investigate the performance of the microgrid. The proposed model has been developed in Matlab-Simulink environment based on an improved control methodology incorporated within the Photovoltaic Generation System (PVGS). Finally, simulation results show the high performance of the proposed method and the recovered power is achieved.